Methionine Metabolism and Ethylene Formation in Etiolated Pea Stem Sections - Schilling, Norbert (1979)
Stem sections of etiolated pea seedlings (Pisum sativum L. cv. Alaska) were incubated overnight on tracer amounts of l-[U-(14)C]methionine and, on the following morning, on 0.1 millimolar indoleacetic acid to induce ethylene formation. Following the overnight incubation, over 70% of the radioactivity in the soluble fraction was shown to be associated with S-methylmethionine (SMM). The specific radioactivity of the ethylene evolved closely paralleled that of carbon atoms 3 and 4 of methionine extracted from the tissue and was always higher than that determined for carbon atoms 3 and 4 of extracted SMM. Overnight incubation of pea stem sections on 1 millimolar methionine enhanced indoleacetic acid-induced ethylene formation by 5 to 10%. Under the same conditions, 1 millimolar homocysteine thiolactone increased ethylene synthesis by 20 to 25%, while SMM within a concentration range of 0.1 to 10 millimolar did not influence ethylene production. When unlabeled methionine or homocysteine thiolactone was applied to stem sections which had been incubated overnight in l-[U-(14)C]methionine, the specific radioactivity of the ethylene evolved was considerably lowered. Application of unlabeled SMM reduced the specific radioactivity of ethylene only slightly.